Relationships between sleep, quality of life and anxiety in patients undergoing cardiac surgeries - Elif Karahan; Hüseyin Demirtaş; Sevim Çelik; İknur Dolu (Universidade de São Paulo, 2024)
Objective: the objective of this study is to examine the relationships between sleep, quality of life and anxiety in patients undergoing cardiac surgeries during the preoperative period, at discharge, two weeks after discharge and three months after discharge. Method: this study had a prospective, descriptive and correlational design and was conducted in a single center. The sample consisted of 68 patients who had undergone cardiac surgeries. The data were collected using an Information Form, the State-Trait Anxiety Inventory, the Richard-Campbell Sleep Questionnaire and the Nottingham Health Profile. Results: the patients' sleep quality increased from moderate to good at each measurement moment after the surgeries, when compared to sleep quality measured at their first hospitalization. While the state anxiety scores decreased at discharge and 2 weeks after the initial hospitalization, they increased to a moderate level 3 months after discharge. There was no significant relationship between anxiety levels and sleep quality at any measurement moment. Additionally, the patients' quality of life was significantly improved 2 weeks and 3 months after discharge. Conclusion: The results of this study showed that the sleep quality of patients who had undergone cardiac surgeries was improved during the postoperative period, and that this improvement exerted a positive effect on their quality of life.